Evolution of Roof Systems in Ancient Coptic Churches: form 4th to 9th Centuries - Maha AbouBakr Ibrahim; Mazen Mohamed Nassef (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Few roof structures remain unscathed from the 4th to 9th centuries in the history of Egyptian architecture generally. The relatively large amount of well-preserved early roof structures in churches in Egypt is used as a point of departure to structurally define medieval Egyptian roof structures. Investigations of actual roof structures along with study of written sources provide the basis for the study, beside site visits if the structure still exists. The structures are defined according to inherited known systems, economics, politics, building materials and semiotics. We can grope an occurring evolution in the design of the churches’ roofs. The medieval roof structures of Coptic churches can generally and concisely be described by tracing them and putting them in a chronological order. This study completes the constructed mental image about that period, and provide architects with simple architectural solutions within communities that enjoy the exitance of multicultures.